(untitled) (Al-Qalaa Journal, 2024)
This study aimed to explore the speech challenges faced by Libyan EFL college students. To achieve this, a qualitative method of data collection was utilized. In particular, 30 (fourth-year) students from the English Language Department at the University of ELMergib were interviewed. After conducting a linguistic analysis of the data, it was found that students faced various difficulties while speaking English. The results indicated that the majority of the participants experienced challenges in this regard. These challenges include limited vocabulary, grammatical errors, incorrect pronunciation, and lack of fluency. The study suggests that it is crucial to train teachers to ensure a successful learning process. Furthermore, the English language curriculum should be tailored to meet the learning needs and requirements of students, with ample focus on listening and speaking courses. Effective teaching and learning strategies should be implemented to enhance students’ language proficiency and extracurricular activities like English clubs should be given emphasis. These activities help to overcome psychological barriers like shyness and hesitation, motivating students to learn and use the language